1995
DOI: 10.1016/0301-0104(95)00219-e
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond time-dependent Stokes shift studies of fluoroprobe in liquid solution

Abstract: We report on a picosecond spectroscopic study of the dynamical Stokes shift of fluoroprobe in the lowest excited state in the solvents diethylether and ethylacetate. Time-resolved emission spectra with a time-resolution of approximately 10 ps are presented. The spectra reflect dynamical Stokes shifts of a few thousand wave numbers within 10-100 ps after the pulsed laser excitation. The time-dependent shifts are representative of the solvation dynamics of fluoroprobe in diethylether and ethylacetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 42 publications
3
47
2
Order By: Relevance
“…Remark that the total Stokes shift in the steady state emission of fluoroprobe dissolved in diethyl ether is about 5100 cm-~ which seems significantly different from the estimated shift of 7000-8000 cm-I in Ref. 18. However, it should be recalled that the latter numbers refers to the low temperature (T~ 160 K) results, whereas the shifts reported here are the room temperature results.…”
Section: Resultscontrasting
confidence: 83%
See 4 more Smart Citations
“…Remark that the total Stokes shift in the steady state emission of fluoroprobe dissolved in diethyl ether is about 5100 cm-~ which seems significantly different from the estimated shift of 7000-8000 cm-I in Ref. 18. However, it should be recalled that the latter numbers refers to the low temperature (T~ 160 K) results, whereas the shifts reported here are the room temperature results.…”
Section: Resultscontrasting
confidence: 83%
“…The solvation times for the fluoroprobe/ethylacetate and the fluoroprobe/diethylether solutions are shorter than those obtained previously for the same systems at lower temperatures [18]. More specifically, in diethylether r s = 1.6 ps at room temperature (this work), while at temperatures ranging from 162 to 201 K, r s decreases from 27 to 10 ps [18]. Thus the shorter time scale measurements are consistent with our previous results which showed that r~ decreases as the temperature increases.…”
Section: C(t) Is Considered To Discuss the Stokes Shift Dynamics Howcontrasting
confidence: 62%
See 3 more Smart Citations